Limb salvage after delayed arterial repair in compound Grade III C fracture humerus: a case report - Ramprasath, Dhurvas Ramlal; Kamalanathan, Major K.; Maheswaran, K. S.; Muthsamy, Mohan Prasad (International Journal of Research in Orthopaedics, 2017)
A combination of brachial artery injury and fracture shaft of humerus is a rare phenomenon. There is a general apprehension regarding survival of a limb after vascular injury. Only few studies exist in literature that discuss about the survival of such limbs. Our case is a 56 years old female patient who presented three hours after sustaining injury in the form of fracture shaft of humerus and complete transection of brachial artery distal to the origin of profunda brachii. Even though Doppler USG done initially revealed flow in the vessels distal to the injury, a CT Angiogram done later revealed cutting of the brachial artery. This prompted us to perform brachial artery exploration and repair. post operatively, digital subtraction angiography showed absence of flow in the brachial artery but limb survived due to extensive collateral circulation. Even after the golden period of vascular repair has lapsed, arterial repair is recommended if there is no evidence of gangrene. This should be supplemented with adequate systemic anticoagulants and/or fasciotomy.